Yorùbá and their Symbolic Means of Communication: A Pragma-Semiotic Analysis of Ààlè - Onipede, Festus Moses (LP2M IAIN Sultan Amai Gorontalo, 2022)
Lots of research had been conducted on àrokò, a symbolic and nonverbal/verbal means of communication among the Yorùbá. While àrokò as a hyponym and ààlè as the super-ordinate have not been studied much. It is in this gap in the literature that this paper attempts a pragma-semiotic analysis of Yorùbá concept of ààlè. Data for the analysis were gathered through participant observation and informal questions technique where these ààlè were used. Mey's (2001) pragmatic acts and Peirce's (1931) symbolic sign in semiotic theory are employed for the analysis. The study revealed that ààlè is used in traditionally motivated contexts characterized by a pract of warning or caution and response that portrays issues of culture, and the indirect acts are employed through contextual features such as reference, shared situational and cultural knowledge, inference and relevance. The Semiotic analysis shows that the signate such as sand, leaves, sticks, fairly-used or unused cutlass, red cloth, òpàrá (a kind of tree grown in West Africa whose seeds are eaten and the bud used for symbolic communication), and cotton wool are one of the significant components of ààlè as symbols of warning or caution. The paper shows that ààlè is a subset of àrokò. While àrokò is the hyponym of symbolic communication among the Yorùbá, ààlè is a super-ordinate of symbolic means of communication among the Yorùbá, mainly for directions and warning. The paper also revealed that two or more objects could be used as ààlè, but their use context will determine the kind of information they are disseminating.